Mindful counselling and psychotherapy : practising mindfully across approaches & issues - Barker, Meg (London : SAGE Publications Ltd, 2014)
Responding to the growing popularity of mindfulness, this is the first cross-modality textbook on using mindfulness approaches in counselling and psychotherapy.
Specialized.
Description based on online resource; title from home page (viewed on November 12, 2015).
Keywords: Mindfulness-based cognitive therapy